Telomere Length, SIRT1, and Insulin in Male Master Athletes: The Path to Healthy Longevity? - Aguiar, Samuel S.; Rosa, Thiago S.; Neves, Rodrigo V. P.; Leite, Patrício L. A.; Maciel, Larissa A.; Gutierrez, Sara D.; Rosa, Erica C.; Andrade, Rosângela V.; Degens, Hans; Korhonen, Marko T.; Lewis, John E.; Simões, Herbert G. (International Journal of Sports Medicine, 2021)
Lower SIRT1 and insulin resistance are associated with accelerated telomere shortening. This study investigated whether the lifestyle of master athletes can attenuate these age-related changes and thereby slow aging. We compared insulin, SIRT1, and telomere length in highly trained male master athletes (n=52; aged 49.9±7.2 yrs) and age-matched non-athletes (n=19; aged 47.3±8.9 yrs). This is a cross-sectional study, in which all data were collected in one visit. Overnight fasted SIRT1 and insulin levels in whole blood were assessed using commercial kits. Relative telomere length was determined in leukocytes through qPCR analyses. Master athletes had higher SIRT1, lower insulin, and longer telomere length than age-matched non-athletes (p<0.05 for all). Insulin was inversely associated with SIRT1 (r=−0.38; p=0.001). Telomere length correlated positively with SIRT1 (r=0.65; p=0.001), whereas telomere length and insulin were not correlated (r=0.03; p=0.87). In conclusion, master athletes have higher SIRT1, lower insulin, and longer telomeres than age-matched non-athletes. Furthermore, SIRT1 was negatively associated with insulin and positively associated with telomere length. These findings suggest that in this sample of middle-aged participants reduced insulin, increased SIRT1 activity, and attenuation of biological aging are connected.
Keywords: aging; running; sirtuins; anti-aging; lifelong exercise